Effect of gold dispersion on the photocatalytic activity of mesoporous titania for the vapor-phase oxidation of acetone - Awate, S. V.; Belhekar, Anagha A.; Bhagwat, S. V.; Kumar, R.; Gupta, N. M. (International Journal of Photoenergy, 2008)
Mesostructured titanium dioxide photocatalyst, having uniform crystallite size (6-12 nm) and average pore diameter of similar to 4.2 nm, was synthesized by using a low-temperature nonsurfactant hydrothermal route, employing tartaric acid as a templating agent. Gold additions from 0.5 to 2wt% were incorporated, either during the hydrothermal process or by postsynthesis wet impregnation. Compared to the impregnation-prepared samples, the samples synthesized hydrothermally contained smaller-size (<= 1 nm) gold clusters occluded in the pores of the host matrix. Whereas CO(2) and H(2)O were the main reaction products in UV-assisted vapor-phase oxidation of acetone using these catalysts, C(2)H(6) and HCO(2)CH(3) were also produced for higher acetone concentrations in air. The conversion of acetone was found to increase with decrease in the size of both TiO(2) and gold particles. In situ IR spectroscopy revealed that titania and gold particles serve as independent adsorption and reaction sites for acetone and oxygen molecules. Acetone molecules adsorb exclusively at TiO(2) surface, giving rise to a strongly adsorbed (condensed) state as well as to the formation of formate- and methyl formate- type surface species. Hydroxyl groups at titania surface participate directly in these adsorption steps. Nanosize gold particles, on the other hand, were primarily responsible for the adsorption and activation of oxygen molecules. Mechanistic aspects of the photochemical processes are discussed on the basis of these observations. Copyright (C) 2008.

Efficient gamma-Fe2O3 catalyst for liquid phase air oxidation of p-hydroxybenzyl alcohol under mild conditions - Garade, Ajit C.; Bharadwaj, M.; Bhagwat, S. V.; Athawale, A. A.; Rode, C. V. (Catalysis Communications, 2009)
gamma-Fe2O3 (maghemite) particles were synthesized at 5 degrees C (LT, low temperature) and 95 degrees C (HT, high temperature) using a simple chemical protocol. The major reflection in XRD was observed to be of the gamma-Fe2O3 phase which was further supported by the XPS analysis. Fe3+ species were responsible for initiation of the oxidation of p-hydroxybenzyl alcohol. SEM revealed that the morphologies of the catalysts were different for samples prepared at two different temperatures. gamma-Fe2O3 (LT) showed the highest catalyst activity (84% conversion) for liquid phase air oxidation of p-hydroxybenzyl alcohol with 94% selectivity to the oxidation products at 370 K and ambient pressure conditions. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Air oxidation; gamma-Fe2O3; p-Hydroxybenzaldehyde; p-Hydroxybenzyl alcohol; scanning electron microscopy